Ministry of Trade And Industry Decree No. 1354 of the Year 2016 On Amending the Export Duty On Certain Kinds Of Scraps And Raw Materials = وزارة التجارة والصناعة قرار رقم 1354 لسنة 2016 فى شأن تعديل رسم صادر على بعض أنواع الخردة والخامات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic